EXPERIMENTAL STUDY OF SURFACE ROUGHNESS IN VIBRO-IMPACT CUTTING OF OPTICAL SLUGS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the article, experimental studies were carried out with the aim of determining the influence of different modes of vibro-impact cutting modes of optical slugs on the roughness of obtained surfaces. From the results obtained during the measurements and their mathematical processing are evaluated the average sizes and  intervals and the parameters of the roughness of treated surfaces.